2009
DOI: 10.1038/ajg.2009.175
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Inflammatory Bowel Disease With Urinary Metabolic Profiling

Abstract: Specific urinary metabolites related to gut microbial metabolism differ between CD patients, UC patients, and controls. The emerging technique of urinary metabolic profiling with multivariate analysis was able to distinguish these cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(164 citation statements)
references
References 48 publications
6
153
1
Order By: Relevance
“…Hippurate was lowest in CD and differed significantly between CD, UC and controls. Formate levels were higher in CD than in UC or controls and 4-cresol sulphate was lower in CD than in UC or controls (Williams et al, 2009). Hippurate has been shown to be modulated according to gut microbes and this difference is likely to reflect changes in intestinal microbes.…”
Section: The Gutmentioning
confidence: 87%
See 1 more Smart Citation
“…Hippurate was lowest in CD and differed significantly between CD, UC and controls. Formate levels were higher in CD than in UC or controls and 4-cresol sulphate was lower in CD than in UC or controls (Williams et al, 2009). Hippurate has been shown to be modulated according to gut microbes and this difference is likely to reflect changes in intestinal microbes.…”
Section: The Gutmentioning
confidence: 87%
“…Urinary metabolites have also been used to distinguish CD and UC in humans (Williams et al, 2009). They found that specific urinary metabolites related to gut metabolism differed between CD, UC and controls.…”
Section: The Gutmentioning
confidence: 99%
“…[23][24][25] Comprehensive metabolic profiles have been generated from biofluids including urine, serum, bile and intact tissue. 24,[26][27][28][29][30][31][32] …”
Section: In Vitro Metabolic Profilingmentioning
confidence: 99%
“…Compliance with treatment was checked by collection of empty blister packs. Subjects were asked to provide a structured dietary and lifestyle history as previously described (19). The primary endpoint was change in ALT after 6 weeks' Rifaximin therapy.…”
Section: Methodsmentioning
confidence: 99%